Usefulness of Diastolic Function Score as a Predictor of Long-Term Prognosis in Patients With Acute Myocardial Infarction - Bae, SungA; Yoon, Hyun Ju; Kim, Kye Hun; Kim, Hyung Yoon; Park, Hyukjin; Cho, Jae Yeong; Kim, Min Chul; Kim, Yongcheol; Ahn, Youngkeun; Cho, Jeong Gwan; Jeong, Myung Ho (Frontiers in Cardiovascular Medicine, 2021)
Background: Left ventricular diastolic function (LVDF) evaluation using a combination of several echocardiographic parameters is an important predictor of adverse events in patients with acute myocardial infarction (AMI). To date, the clinical impact of each individual LVDF marker is well-known, but the clinical significance of the sum of the abnormal diastolic function markers and the long-term clinical outcome are not well known. This study aimed to investigate the usefulness of LVDF score in predicting clinical outcomes of patients with AMI. Methods: LVDF scores were measured in a 2,030 patients with AMI who underwent successful percutaneous coronary intervention from 2012 to 2015. Four LVDF parameters (septal e′ ≥ 7 cm/s, septal E/e′ ≤15, TR velocity ≤ 2.8 m/s, and LAVI ≤ 34 ml/m2) were used for LVDF scoring. The presence of each abnormal LVDF parameter was scored as 1, and the total LVDF score ranged from 0 to 4. Mortality and hospitalization due to heart failure (HHF) in relation to LVDF score were evaluated. To compare the predictive ability of LVDF scores and left ventricular ejection fraction (LVEF) for mortality and HHF, receiver operating characteristic (ROC) curve and landmark analyses were performed. Results: Over the three-year clinical follow-up, all-cause mortality occurred in 278 patients (13.7%), while 91 patients (4.5%) developed HHF. All-cause mortality and HHF significantly increased as LVDF scores increased (all-cause mortality–LVDF score 0: 2.3%, score 1: 8.8%, score 2: 16.7%, score 3: 31.8%, and score 4: 44.5%, p<0.001; HHF–LVDF score 0: 0.6%, score 1: 1.8%, score 2: 6.3%, score 3: 10.3%, and score 4: 18.2%, p<0.001). In multivariate analysis, a higher LVDF score was associated with significantly higher adjusted hazard ratios for all-cause mortality and HHF. In landmark analysis, LVDF score was a better predictor of long-term mortality than LVEF (area under the ROC curve: 0.739 vs. 0.640, p<0.001). Conclusion: The present study demonstrated that LVDF score was a significant predictor of mortality and HHF in patients with AMI. LVDF scores are useful for risk stratification of patients with AMI; therefore, careful monitoring and management should be performed for patients with AMI with higher LVDF scores.